The coffee sector of Costa Rica: production, organizational and institutional aspects of industry - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This document explains on economic importance of coffee the coffee market, organization with the coffee sub-sector, support institutions and relationship between the various actors in the coffee industry.